Strichjungen-Gespräche : zur Soziologie jugendlicher Homosexuellen-Prostitution. - Schmidt-Relenberg, Norbert; Kärner, Hartmunt; Pieper, Richard (Darmstadt : Luchterhand, 1975)
Fonds Suzan Daniel (FSD)
Duits
Monografie